A facile band alignment with sharp edge morphology accelerating the charge transportation for visible light photocatalytic degradation: A multiplex synergy. (December 2019) - Shakeel, Muhammad; Yasin, Ghulam; Arif, Muhammad; Zhang, Xiaorong; Abbas, Zaheer; Khan, Shafiullah; Rehman, Wajid; Zaman, Umber; Ul Haq Khan, Zia; Li, Baoshan
Highlights: Ag-AgBr-TiO2 -g-C3 N4 heterostructures is designed and applied for the photocatalytic degradation of RhB and MB. The hydrothermal treatment has remarkable effect on the structure and morphology. The formation of interface between Ag-AgBr and TiO2 -g-C3 N4 leads to longer lifetime of the excited electron. The photocatalyst exhibit excellent ability of photodegradation compared with pure sample with significant stability. Abstract: Heterojunction photocatalysts has gained much attention in last decade due to their high photo-catalytic activity. Therefore, we have synthesized Ag-AgBr/TiO2 -g-C3 N4, a visible light photo-catalyst via. single step micro-emulsification followed by controlled hydrothermal and calcination treatment. Simultaneous crystallization of TiO2 and conversion of bulk g-C3 N4 into nano-sheets took place by hydrothermal and calcination respectively. The degradation efficiency of Ag-AgBr/TiO2 -g-C3 N4 for MB and RhB was quite high with rate constant k = 0.120 & 0.156 min −1 than TiO2 -g-C3 N4 (k = 0.035 & 0.053 min −1 ) and Ag-AgBr/TiO2 (k = 0.015 & 0.016 min −1 ) respectively. This phenomenon was explained in terms of multiplex synergy such as localized surface plasmon resonance (LSPR) of AgNPs and absorption of visible light by AgBr, further the interfacial electron transferring within Ag-AgBr-TiO2 and g-C3 N4 has equal contribution apart. The suitable adjustment of band edge potential ensures the enhance separation of electron-hole pairs providing an excellent photocatalytic activity. Moreover Ag-AgBr/TiO2 -g-C3 N4 exhibited good photo stability and reusability due to plasmonic properties of AgNPs.